The effect of the SQ3R learning method on reading skills of Buddhist sunday school students’ in west Tulang Bawang Regency - Sri Wahyuningsih; Ayu Andriyaningsih; Sutiyono Sutiyono (Universitas Sebelas Maret, 2025)
Low interest and reading ability among students remain a major challenge in the learning process, including at the Buddhist Sunday School in West Tulang Bawang Regency. Field observations reveal that many students have difficulty understanding the content of texts, quickly become bored when reading, and have difficulty staying focused and concentrating during the reading process. These problems indicate an urgent need for the application of learning methods that are not only effective and efficient, but also enjoyable and structured, in order to help improve students' reading skills and overall learning motivation. One method that is considered relevant and suitable for overcoming this challenge is the SQ3R method, which stands for Survey, Question, Read, Recite, and Review. This method is designed to encourage students to actively engage with reading materials through a systematic, gradual, and organised approach, so that students can understand the content of the reading deeply and not just read passively. The purpose of this study was to determine the effect of the SQ3R learning method on the reading skills of Buddhist Sunday School students and to measure the extent to which this method contributes to improving their reading abilities. This study used a quantitative approach with a survey method and involved 44 students as respondents. The instrument used was a Likert scale questionnaire with five indicators corresponding to the stages in the SQ3R method. The results showed that this method had a significant effect, with a contribution of 53.2%, while the remaining 46.8% was influenced by other external factors. These findings confirm that SQ3R is a practical and effective method for improving reading literacy in a religious education setting.